2016
DOI: 10.1080/13562517.2016.1183612
|View full text |Cite
|
Sign up to set email alerts
|

A diffractive reading of dialogical feedback through the political ethics of care

Abstract: With regard to improving higher education feedback practices, there is an increasing interest in using the efficacy of dialogue rather than the more traditional unidirectional approaches. We build on this impetus by considering how the ethics of care can be used to analyse the dialogical aspects of feedback. By diffractively reading insights of Boud and Molloy [2013a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Using Google Drive both in the course and in subsequent work facilitated writing together and dialogic interaction on our writing. There was a parallel process of participants becoming comfortable with giving and receiving feedback on Google Docs and developing relationships of trust as well as critical engagement as described in our paper (Bozalek et al, 2016). Christie et al (2007) argue that an educational CoE is likely to benefit from incorporating a wide range of perspectives.…”
Section: Relationshipsmentioning
confidence: 91%
See 3 more Smart Citations
“…Using Google Drive both in the course and in subsequent work facilitated writing together and dialogic interaction on our writing. There was a parallel process of participants becoming comfortable with giving and receiving feedback on Google Docs and developing relationships of trust as well as critical engagement as described in our paper (Bozalek et al, 2016). Christie et al (2007) argue that an educational CoE is likely to benefit from incorporating a wide range of perspectives.…”
Section: Relationshipsmentioning
confidence: 91%
“…Our research is guided by a scholarly approach involving reflective practice conducted by researchers who are directly involved in the research setting, referred to as 'insider research' in higher education (Trowler, 2012;Robson, 2002). In a previous paper (Bozalek et al, 2016), we examined our experiences on the ET course through a political ethics of care framework (Tronto, 1993). In this paper we use a framework of factors considered significant when attempting to build a CoE (Christie et al, 2007;Cassidy et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Joan Tronto's political ethics of care (1993,2013) is gaining attention in the development of higher education professional development practices (Bozalek et al 2014;Bozalek et al 2016;Zembylas, Bozalek and Shefer 2014). Bozalek et al (2014) also found that the ethics of care provided a meaningful framework through which participants in a HEI professional development programme could evaluate their practice.…”
Section: Ethics Of Carementioning
confidence: 99%